Determinan Produktivitas Usahatani Jagung (Zea mays. L) - Dahring, Andi Trisnaidar; Amrullah, A.; Viantika, Ni Made (Jurnal Sosial Ekonomi Pertanian, 2025)
This study aims to analyze the factors that influence the productivity of maize farming in Marioriwawo District, Soppeng Regency. The location was determined by purposive sampling because Marioriwawo Sub-district is one of the corn production centers in Soppeng Regency with a high harvest area and production. The sample was determined using the accidental sampling method with a total sample size of 96, calculated using the Cochran formula. The analytical tool used was binary logistic regression analysis. The estimation of this model shows that of the 13 independent variables tested, 8 variables partially have a significant effect on the productivity of corn farming, including land area, seeds, urea fertilizer, NPK fertilizer, weeding labor, pest and disease control labor, non-formal education, and farming experience. In contrast, other variables such as herbicide cost, insecticide cost, fertilization labor, age, and formal education do not significantly affect the productivity of maize farming in Marioriwawo District, Soppeng Regency.